Astrobiological implications for Perchlorates on Mars. Issue 3 (8th February 2017) - Mancinelli, R. L.
Abstract : Astrobiology is the study of the past, current and future potential for life in the Universe and has been fascinated with the possibility of life on Mars since the late 1800s. Because of the potential for life on Mars it is vital to understand the role perchlorates may play in that potential.